(untitled) (Medical Forum Monthly, 2026)
Objective: To identify the knowledge and perceptions of participants regarding the poppy seeds (khash-khash) consumption and false-positive opioid urine test results and related consequences Study Design: Cross-sectional studyPlace and Duration of Study: This study was carried out in major urban cities of Pakistan from August to November 2025. Methods: A structured questionnaire based at Google Forms was shared with 384 participants. The questionnaire contained 3 sections that measured demographic variables, knowledge and perceptions of participants regarding poppy seed (khash-khash) consumption, false-positive opioid urine test and related consequences. Subsequently, twenty participants of different age groups were selected who regularly consumed poppy seeds provided urine samples at 6 and 24 hours after ingestion. Samples were first screened for opioids using enzyme immunoassay (EIA). Results: The results demonstrate that (89.84%) participants reported widespread consumption of poppy seeds. Nonetheless, awareness of the risk of false-positive results was extremely low. A large proportion of the respondents (77.6%) lacked the awareness that poppy seeds lead to a false positive urine test for opioids. Moreover, 51.2% of the participants felt that the current urine drug tests are not adequate to distinguish between the use of opiates and consumption of poppy seeds. Majority of the participants were of the opinion that this false positive opioid drug can result in dismissal, emotional distress, legal actions and loss of reputation. All participants who regularly consumed poppy seeds were confirmed to have false positive urine test for opioids Urine tests of opioids were detected to be false positive using enzyme immunoassay (EIA) with a cutoff of 300 ng/mL, and positive results were confirmed using LC-MS/MS. Conclusion: This study confirms a significant awareness gap and validates poppy seed–induced false-positive opiate tests. Targeted education and policy-level improvements in drug testing protocols are urgently needed to ensure fairness and accuracy.